A HUMAN RIGHTS-BASED COMMUNICATION WIRETAPPING POLICY MODEL FOR LAW ENFORCEMENT IN INDONESIA - Gunawan Widjaja; Adrian Bima Putra (ADISAM PUBLISHER, 2025)
This research discusses the model of human rights-based communication tapping policy in law enforcement in Indonesia. The fragmentation of wiretapping regulations in various laws such as the Telecommunications Law, ITE Law, and KPK Law has created legal uncertainty and opened opportunities for violations of citizens' privacy rights. This study uses a literature review method to analyse norm conflicts in wiretapping regulations and formulate a policy model that meets accountability and privacy protection standards. The results show that wiretapping should be conducted based on court permission, with independent supervision, restrictions on scope and duration, and an effective complaint mechanism for victims of illegal wiretapping. Regulatory harmonisation is needed through the establishment of a special law on wiretapping that integrates international human rights principles and accountability, so that wiretapping can be an effective law enforcement instrument without compromising the fundamental rights of citizens.